Respostas
respondido por:
15
(3x⁴) . (- 5x³) =
= 3 . (- 5) . x⁴ . x³ =
= - 15x⁴⁺³ =
= - 15x⁷
= 3 . (- 5) . x⁴ . x³ =
= - 15x⁴⁺³ =
= - 15x⁷
respondido por:
10
(3x⁴) . (-5x³) = - 15x⁷
Explicação:
# multiplica os sinais --> (+) . (-) = (-)
# multiplica os coeficientes ---> 3 . 5 = 15
# multiplica as letras --> x⁴ . x³ = x⁴⁺³ = x⁷
Explicação:
# multiplica os sinais --> (+) . (-) = (-)
# multiplica os coeficientes ---> 3 . 5 = 15
# multiplica as letras --> x⁴ . x³ = x⁴⁺³ = x⁷
JaumMeiaUm:
Obrigado você m ajudou bastante
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás